The Influence of Various Concentrations of Old Coconut Water Waste(Cocos nucifera L) as an Alternative Growth Media of Escherichia coli - Zulyamin Kimo; Eko Susetyorini; Lud Waluyo (Pancaran Pendidikan, 2017)
Growth medium of bacteria commonly used synthetic medium such as nutrient agar (NA). This synthetic medium was still imported and the price very expensive, therefore, to search an alternative medium needs to be done in order to reduce dependence on imported medium. Alternative medium can be obtained from natural resource that contain nutrient similar as medium in general, such old coconut waste water (Cocos nucifera L). Old coconut water contains glucose, sucrose, protein, minerals, and vitamins. This potential can be used as an alternative growth medium for microorganisms who ferment sugars like Escherichia coli.This study aims to determine the effect of various concentrations of old coconut wastewater (Cocos nucifera L) as an alternative Escherichia coli growth medium. The sample used is old coconut (Cocos nucifera L) wastewater that obtained from Merjosari Market, Malang by setting concentration of 0%, 25%, 50%, 75% and 100%. The result shows old coconut  wastewater medium(Cocos nucifera L) with concentration of 100% has a highest growing number colony of  Escherchia coli, that are 334 x 105. This ability is not much different from used nutrient agar as a omparative medium with total colonies growth are 344 x 105. The concentration of 0% there is no bacterial growth at all. Conclusion from this study is there are growth effects from used various concentrations old coconut wastewater (Cocos nucifera L) as an alternative growth medium of  Escherchia coli and old coconut waterwaste with 100% concentration is the most effective to grow the Eschericia coli.